1998
DOI: 10.1159/000007935
|View full text |Cite
|
Sign up to set email alerts
|

Isolated So-Called Apraxia of Eyelid Opening: Report of 10 Cases and a Review of the Literature

Abstract: So-called apraxia of eyelid opening (scAEO) has been described chiefly in the context of extrapyramidal disorders. We described 10 new patients with scAEO developing in the absence of any other CNS sign and reviewed the 11 cases with isolated scAEO reported in the literature. Combining our patients and those from the literature, peak age at onset was in the 6th decade and there was a female preponderance of 2:1. The characteristic inability to initiate lid elevation was frequently associated with failure to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…Since genetic research studies should rely on correct diagnoses, we explicitly avoided using family history reported by proband for identifying dystonia among unexamined relatives because this method may be highly insensitive and incurs the risk of misclassifying relatives affected by movement disorders other than dystonia [26]. Nor did we consider as definite dystonia subtle motor findings presenting a diagnostic challenge [20][21][22][23]. A further bias may have arisen from examining only a proportion of relatives, a common problem in late-onset disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since genetic research studies should rely on correct diagnoses, we explicitly avoided using family history reported by proband for identifying dystonia among unexamined relatives because this method may be highly insensitive and incurs the risk of misclassifying relatives affected by movement disorders other than dystonia [26]. Nor did we consider as definite dystonia subtle motor findings presenting a diagnostic challenge [20][21][22][23]. A further bias may have arisen from examining only a proportion of relatives, a common problem in late-onset disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of dystonia was not attributed to motor findings that are not considered into the full spectrum of dystonia. These were excessive blinking with no evidence of the Charcot's sign [20], isolated apraxia of eyelid opening [21], unusual tight hand gripping with writing or other manual activities [20], shoulder elevation without significant limitation of shoulder movement [22], and isolated tremor with no signs of dystonia [23]. All relatives considered to be affected were videorecorded.…”
Section: Subjectsmentioning
confidence: 99%
“…Introduction Automatic-voluntary dissociation of orofaciolingual-pharyngeal motility is one of the hallmarks of the biopercular Foix-ChavanyMarie syndrome [1,2]. While automatic-voluntary dissociation of movements of the upper extremities (mostly apraxias) or eyelid movements is well known [3,4], similar deficits of other cranial movements have been reported but less well studied [5]. Apraxia is defined as the inability to perform correctly voluntary learned skilled movements upon request in an experimental setting or everyday life (anterior of frontal apraxia), to pantomime (posterior or parietal apraxia), to use objects (on command, imitation or presentation) or to imitate correctly meaningful or meaningless gestures performed by the examiner [6].…”
Section: Discussionmentioning
confidence: 99%
“…Apraxia can result from lesions of the dorsolateral frontoparietal-subcortical circuits interrupting the flow of information at any level between the complex motor programs of the frontal cortical areas and the sensorimotor areas allowing external cues to guide motor behavior [6]. Unfortunately, the definition of apraxia has been extended for apraxia of eyelid opening to a syndromic entity of what is either supranuclear eyelid paresis with automatic-voluntary dissociation and/or pretarsal blepharospasm [3,4]. In the FoixChavany-Marie syndrome [1,7], or biopercular syndrome, pseudo- bulbar palsy with central voluntary palsy is reported, preserving automatic and emotional movements [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…The site of the anatomical lesion in LOA is unclear. Its strong association with parkinsonism and occasional levodopa-responsiveness suggests dysfunction of the influence of the basal ganglia on brainstem structures regulating lid function (Defazio et al, 1998). Functional imaging studies further suggest impairment of frontostriatal connections (Suzuki et al, 2003).…”
Section: Apraxia Of Lid Openingmentioning
confidence: 99%